Improving Educators Digital Literacy Through Assistance in the Development of Lectora Inspire- Based Mathematics Learning Media - Robiatul Adawiyah; Arika Indah Kristiana (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
The competence of an educator is the main key to the success of a lesson. The problems that exist in schools partner are that educators complain about the low numeracy skills of students and the minimal use of technology in learning. Teachers are the main key to the success of nursery human resources. Teachers are required to be more creative, innovative and inspiring in designing quality learning activities to welcome Indonesia's golden generation, especially in learning mathematics. Digital-based learning media can attract students to be more enthusiastic about learning mathematics. One of the software that can be used to develop mathematics learning media is the Lectora Inspire software. In order to develop a technology-assisted learning media, educators' digital competencies really need to be built so that educators can be more creative in creating interesting and not boring learning. Therefore, a teacher competency development assistance is needed, where a forum for the development of pedagogic and professional competencies for teachers at SMPN 6 Tanggul in Kramat Sukoharjo Village. Community service activities are packaged by applying the ADDIE (Analysis-Design-Development-Implementation-Evaluation) training model. Based on the results of the pretest and posttest, the percentage of N-Gain was 76%. Based on the category of interpretation of the effectiveness of N-Gain, the value is included in the effective category because it meets the value of . That is, learning media based on lecturera inspire is effective in increasing student understanding.